13C labeling unravels carbon dynamics in banana between mother plant, sucker and corm under drought stress - Vantyghem, Mathilde; Beelen, Eline; Hood-Nowotny, Rebecca; Merckx, Roel; Dercon, Gerd (Frontiers in Plant Science, 2023)
Banana is a perennial crop and typically consists of a mother plant and one or more suckers that will serve as the next generation. Suckers are photosynthetically active, but also receive photo-assimilates from the mother plant. While drought stress is the most important abiotic constraint to banana cultivation, its effect on suckers or banana mats as a whole remains unknown. To investigate whether parental support to suckers is altered under drought stress and to determine the photosynthetic cost to the parental plant, we conducted a 13C labeling experiment. We labeled banana mother plants with 13CO2 and traced the label up to two weeks after labeling. This was done under optimal and drought-stressed conditions in plants with and without suckers. We retrieved label in the phloem sap of the corm and sucker as soon as 24 hours after labeling. Overall, 3.1±0.7 % of label assimilated by the mother plant ended up in the sucker. Allocation to the sucker seemed to be reduced under drought stress. The absence of a sucker did not enhance the growth of the mother plant; instead, plants without suckers had higher respiratory losses. Furthermore, 5.8±0.4 % of the label was allocated to the corm. Sucker presence and drought stress each led to an increase in starch accumulation in the corm, but when both stress and a sucker were present, the amount was severely reduced. Furthermore, the second to fifth fully open leaves were the most important source of photo-assimilates in the plant, but the two younger developing leaves assimilated the same amount of carbon as the four active leaves combined. They exported and imported photo-assimilates simultaneously, hence acting as both source and sink. 13C labeling has allowed us to quantify source and sink strengths of different plant parts, as well as the carbon fluxes between them. We conclude that drought stress and sucker presence, respectively causing a reduction in supply and an increase in carbon demand, both increased the relative amount of carbon allocated to storage tissues. Their combination, however, led to insufficient availability of assimilates and hence a reduced investment in long-term storage and sucker growth.